Global Bifurcation of Positive Solutions of Asymptotically Linear Elliptic Problems. (25th May 2014) - Ma, Ruyun; Lu, Yanqiong; Chen, Ruipeng
Abstract : We are concerned with determining values of λ, for which there exist positive solutions of the nonlinear elliptic problem - Δ u = λ a ( x ) f ( u )     in     Ω, ∂ u / ∂ n + b ( x ) g ( u ) = 0     on     ∂ Ω . The proof of our main results is based upon unilateral global bifurcation theorem of López-Gómez.